Analiza audytywno-akustyczna danych językowych z wykorzystaniem programów komputerowych: EXMARaLDA i Praat - Marta Rogozińska (Linguistische Treffen in Wrocław)
The purpose of this article is to present selected features of two computer programs that can be used to perform auditory-acoustic analysis of linguistic data: EXMARaLDA and Praat. Depending on the research interests and the degree of precision of the linguistic description (from recording the wording of the utterances to the additional description of suprasegmental and prosodic phenomena and phonetic analysis), these programs allow the transcription, annotation and analysis of speech. Due to their functionality, they can be used separately, providing technical support for in-depth auditory (mainly EXMARaLDA) or acoustic (mainly Praat) analysis, or together, allowing visualisation or objectification of auditory impressions. EXMARaLDA is particularly suitable for speech analysis, as it can preserve and transcribe the sound of very long utterances, select specific phenomena, and create and manage text corpora. For acoustic analysis, Praat allows detailed analysis of the physical properties of speech, including fundamental frequency analysis, sound intensity analysis, spectral analysis, formant analysis or voice quality analysis. Depending on the research question, the two methods (analysis of auditory impressions and analysis of the physical properties of speech) can be used independently or in parallel. The research material obtained in this way can contribute to in-depth analysis of linguistic data and is used not only in speech and communication research in the broadest sense, but also in interdisciplinary research combining different disciplines and research approaches. The article is of a practical nature and aims to familiarise the interested reader with selected functions for qualitative and quantitative (signal) analysis of speech.